Saving China’s dogs: social transformation and moral conflicts in Chinese society - Pettier, Jean-Baptiste (Critical Asian Studies, 2021)
To be considered worthy of society’s protection is not the objective consequence of an inherent quality but the result of a social process. This article examines this observation through the case of canine welfare in China. Popular defense of dogs against brutalization and consumption, as well as state regulations, have become common in China in recent years, generating conflicts over the value attributed to dogs. To understand the circumstances behind and broader implications of activists’ support for protecting dogs, this article identifies elements that are determinant: framing; prioritization; the relationship between protectors and protected; and the socio-political background of these campaigns.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Animal rights campaigns; animal welfare; dog protection